The influence of alendronate therapy on the quality of life in postmenopausal women with reduced bone mineral density - Bączyk, Grażyna; Formanowicz, Dorota; Kleka, Paweł; Samborski, Włodzimierz (Journal of Medical Science, 2017)
Introduction and objective: The aim of the study was to evaluate the effect of treatment on the quality of life (QoL) in postmenopausal women characterized by the reduced BMD. Material and methods: Postmenopausal women (n=102), mean age (65.09±5.6 years) were included in this study. The participants were divided into two groups, depending on the treatment or lack of treatment. For assessment of their QoL, QUALEFFO-41 scale and WHOQOL-100 scale were used. Results: Mean values of the QUALEFFO-41 scale of women who used alendronate were significantly lower than those found in subjects not treated with this drug in the following areas: pain (p=0.03), ADL (p=0.03), jobs around the house (p=0.01), mobility (p=0.01), health perception (p=0.03), emotional function (p= 0.007) and total QoL (p=0.005). The mean values of the WHOQOL-100 scale almost did not differ significantly between both groups of studied patients. An exception was the level of independence, with mean values of women not receiving bisphosphonates being significantly higher than those of patients using bisphosphonates therapy (p=0.04). Conclusions. Quality of life assessment of women with osteoporosis and osteopenia using a specific scale and general scale can be a valuable clue in the planning of treatment, nursing care and psychological care.